Political Preferences and Public Sector Outsourcing - Mikael Elinder; Henrik Jordahl (Research Institute of Industrial Economics (IFN), 2011)
There are several theoretical accounts of public sector outsourcing. We note that leading theories give different predictions of the influence of political variables and test the predictions on a Swedish data set in which outsourcing varies between municipalities and over time as well as between services. Our identification strategy focuses on two services with similar contracting problems and local market conditions: preschools and primary schools. We study a period in which Swedish municipalities had full discretion in the provision of preschools, while their influence on the provision of primary education was limited by a national voucher system. The comparison of preschools and primary schools in a difference-in-differences model suggests that the political color of the ruling majority matters for outsourcing, which is consistent with the citizen candidate model of representative democracy.
Keywords: D23; H11; H40; L33; 330; Outsourcing; Ideology; Public provision; Contracting out; Politische Entscheidung; Kommunale Dienstleistung; Outsourcing; Schweden